ESTIMASI OUTPUT DAN IDENTIFIKASI GEN HORMON PERTUMBUHAN BABI DI KABUPATEN TABANAN PROVINSI BALI - , Bayu Dewantoro Putro Soewandi, Prof. Dr. Ir. Sumadi., MS. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of the study was to identify output of pig in Tabanan regency and to know growth hormone gene in pigs. The samples were collected from 150 traditonal breeders in 5 districts in Tabanan residence and the samples for analysis moleculer of growth hormone gene were 40 (2 to 3 months) Bali and Landrace pigs (20 Bali pigs and 20 Landrace pigs). The collection data included identifcation of breeders, composition and reproduction of pig, body size and characteristic eksterior of pig. Result of study indicated that the value of natural increase value (NI) is Bali pigs 60,93% and Landrace pigs 116,36%. Value of net replacement rate (NRR) in male and female Bali and Landrace pigs on male and female are 9.910,71 and 1.416,67% and 12.666,67 and 1.773,93%. Result of output male and female Bali pig 30,78 and 23,58% (equivalent to 360 and 114 pigs) and male and famale Landrace pig 45,57 and 70,49% (equivalent to 6.722 and 10.009 pigs). The result of moleculer analysis shows that from 40 pig that is monomorphic (genotipe h+h+). Inconclusion, estimation output in Bali and Landrace pigs were moderate. GH gene in Bali and Landrace pigs were monomorphic and can not be used as moleculer marker.